2017
DOI: 10.1177/1043454217735829
|View full text |Cite
|
Sign up to set email alerts
|

Parent Perspectives on Pain Management in Preschool-Age Children With Sickle Cell Disease

Abstract: Pain episodes occur for many preschoolers with sickle cell disease (SCD), but little is known about parent perceptions of managing pain episodes in young children. We surveyed parents of young children with SCD who had managed pain episodes in the past year to assess their management and satisfaction with their strategies, challenges of pain management, and interest in additional education. Parents were recruited from health maintenance visits at a SCD specialty clinic. Forty-two of 51 parents (82%) of 2- to-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…This compares well with previous reports evaluating patient-perceived benefits of pain relief, particularly with use of CAM in conjunction with conventional treatment of SCD. 25,28 However, this study found that the respondents' perception of effectiveness occurred irrespective of whether drugs were used alone, or in combination with CAM as relief for pain episodes. This finding also puts to question the additional benefits of some forms of CAM, particularly massage whose beneficial effects evaluated by previous studies were conflicting, probably due to application by patients and relatives who are mostly non-professionals.…”
Section: Articlementioning
confidence: 72%
See 2 more Smart Citations
“…This compares well with previous reports evaluating patient-perceived benefits of pain relief, particularly with use of CAM in conjunction with conventional treatment of SCD. 25,28 However, this study found that the respondents' perception of effectiveness occurred irrespective of whether drugs were used alone, or in combination with CAM as relief for pain episodes. This finding also puts to question the additional benefits of some forms of CAM, particularly massage whose beneficial effects evaluated by previous studies were conflicting, probably due to application by patients and relatives who are mostly non-professionals.…”
Section: Articlementioning
confidence: 72%
“…Although with prevalence rates of 14-67% reported by previous studies, massage was one of the leading CAM employed for pain relief in SCD. [26][27][28] On the contrary, prevalence rates of 2.0% and 4.0% reported in studies carried out in Lagos, South-west Nigeria indicate a low utilization of massage in that region, with predominance of biological products' as CAM. 25,29 It is also noteworthy that, unlike studies from other parts of the world, none of the respondents in our study admitted to use of cer- tain types of CAM such as acupuncture, hypnosis, homeopathy, biofeedback, and other cognitive strategies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…(Asnani et al, 2016). Smith et al (2018) reported that most parents used methods of giving a hot or warm bath and massaging. Dampier et al (2002) reported that parents generally used the nonpharmacological methods of allowing the child to watch TV, reading, talking, putting the child to sleep, giving the child a hot bath, massaging, praying and relaxation for home management of pain in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Of children diagnosed with SCD, 20% report persistent pain (Connolly et al, 2019). Parents also note difficulty encouraging their children to engage in activities when they are in pain (Smith et al, 2018). Subsequently, 35% of children with SCD miss at least 20 days of school per year (Connolly et al, 2019).…”
Section: School Access and Inclusionmentioning
confidence: 99%